Integrated Economic and Environmental Assessment of Nitrogenous Fertilizer Application in Canadian Prairies - Kulshreshtha, Suren (Journal of Agriculture and Environment, 2010)
Adoption of mitigation measures to reduce greenhouse gas emissions may affect other members of the society, producing a situation of trade-offs. In this study, such a trade-off is has been analyzed using three aspects of the Canadian society: producers (farm level adopter), environment (through reduction in the GHG emissions),; and regional economy (including rest of the society through lost / gained economic activities). The nutrient management strategy involving the switching nitrogen fertilizer application from a combination of fall and spring application to a 100 percent spring application. Results suggest that the adoption of such a measure creates a 'win-win' situation, being both environmentally and economically desirable. Under the scenario, fertilizer expenditures decreased by $43 million (giving rise to an equivalent increase in farm income), GHG emissions (in CO2E) by 2.15 percent of the 2000 level of emissions, Canadian economy as a whole showed improvements, although on a regional basis the results were mixed. Key words: Canadian prairie agriculture; Greenhouse gases; Mitigation; Nitrogen fertilizer Use; Trade-off analysis The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 70-82 Uploaded date: 15 Septembre, 2010